MENINGKATKAN KEMAMPUAN MENYIMAK CERITA RAKYAT BERBASIS MULTIMEDIA INTERAKTIF ADOBE FLASH KELAS V SD NEGERI 2 KADIPIRO - Safitri Idawati; Heru Purnomo; Ningrum Perwitasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was prepared with the aim of improving the ability to listen to interactive multimedia folktales in Adobe Flash class V SD Negeri 2 Kadipiro. The listening skills referred to in the research are the skills of students in understanding something. This type of research is Classroom Action Research (PTK), where teachers are the implementers of learning while researchers are observers. The design of this study uses the Kemmis and Mc. Taggart models. This research was carried out in the even semester of the 2023/2024 school year, namely in May. The subject of this study is class V students of SD Negeri 2 Kadipiro consisting of 22 students. The object of this research is the ability to listen to folklore. The data collection technique uses observation and interviews. The data is analyzed descriptively and presented in the form of tables and graphs. The results of the study showed that there was an increase in student learning activity that occurred in cycle I and cycle II. Thus, the use of Adobe Flash interactive multimedia to improve the ability to listen to folklore in the Indonesian subject class V of SD Negeri 2 Kadipiro.